2018
DOI: 10.1007/s00203-018-1520-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sialidase activity and cellular invasion by the bacterial vaginosis pathogen Gardnerella vaginalis

Abstract: Bacterial vaginosis is a genital tract infection, thought to be caused by transformation of a lactobacillus-rich flora to a dysbiotic microbiota enriched in mixed anaerobes. The most prominent of these is Gardnerella vaginalis (GV), an anaerobic pathogen that produces sialidase enzyme to cleave terminal sialic acid residues from human glycans. Notably, high sialidase activity is associated with preterm birth and low birthweight. We explored the potential of the sialidase inhibitor Zanamavir against GV whole ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
(76 reference statements)
3
32
0
Order By: Relevance
“…Similarly, the genomospecies had vastly different repertories of accessory genomes, except the group that contained GS05, GS04, and GS09. These differences may be important for adaptation to the vaginal microenvironment or BV pathology because some of the genes driving this difference include those known for virulence (e.g., sialidases) (44,45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the genomospecies had vastly different repertories of accessory genomes, except the group that contained GS05, GS04, and GS09. These differences may be important for adaptation to the vaginal microenvironment or BV pathology because some of the genes driving this difference include those known for virulence (e.g., sialidases) (44,45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of Gardnerella sialidases in adhesion has not been demonstrated directly, although it has been reported that inhibition of sialidase activity in Gardnerella strain JCP8066 by an antiviral drug (Zanamavir) resulted in reduction of adherence to vaginal epithelial cells in vitro (12). Gardnerella spp.…”
Section: Characterization Of a Poly-c Homopolymer In Nanh3mentioning
confidence: 99%
“…Metabolomics combined with proteomic approaches represents one of the most important postgenomic analyses to investigate changes in cell metabolism and identify biomarkers during the course of infection inside macrophages (Singh et al, 2015 ). Several studies have demonstrated an association between host cell metabolism and response to different pathogens, including Leishmania (Lamour et al, 2012 ; Govinden et al, 2018 ; Price et al, 2018 ; Reddy et al, 2018 ).…”
Section: Proteomic Contribution To Understanding the Macrophage Respomentioning
confidence: 99%